Dinámica de crecimiento de veintinueve especies forestales establecidas y análisis de las propiedades físicas y químicas del suelo en el Jardín Botánico el Padmi, Zamora Chinchipe - Gaona Ochoa, Telmo Galecio (2014)
This research was conducted at the Botanical Garden of the Fifth Padmi The National University of Loja, located in the parish of Los Encuentros Yantzaza canton in the province of Zamora Chinchipe. The investigation determined the growth of 29 tree species in D1,30 m (cm), height (m) and volume (m3). Besides survival (%), crown diameter (m), cup-shaped canopy openness (%) rates ratio (%) and living space (m2) was evaluated. Analysis of physical and chemical soil where they were established forest species properties was also performed. The trial design is in blocks, each block a species with 18 individuals at a spacing of 3 x 3 m planted two periods in 2005 (11 species) and 2009 (18 species) was established. The purpose of the research is to identify the species of greatest growth and survival to establish forest plantations and agroforestry systems with rural communities, local governments, institutions of the southern Amazon, to curb pressure on native forests. The species established in 2005, demonstrating greater growth and survival are Cedrelinga cateniformis, Persea sp., Huartea glandulosa, Lafoensia cf. punicifolia, Platymiscium pinnatum, Vitex cymosa and Clarisia biflora, these species are now recommended for the establishment of plantations and agroforestry systems, to present better growth in D1,30, height and volume, considering the similar features of the site. The species established in 2009 to further growth and survival are presented: Nectandra sp, Terminalia oblonga, Apeiba membranacea, Guarea kunthiana, Caryodendron orinocense, Terminalia amazonia, Albizia sp., Ochroma pyramidale, Piptocoma discolor, Heliocarpus americanus, Aspidosperma laxiflorum, Pouteria capasifolia, Cedrela odorata and Clarisia racemosa; these species, it is recommended to establish forest plantations and / or SAF. The diameter and cup-shaped species established in the year 2005, seven presented the best cup diameters greater than 2,5 m, and how frequently is rounded, umbrella and ellipsoidal, while forest species established in year 2009, eight have better growth and cupped most predominant are rounded and ellipsoidal pendant. The slenderness ratio states that values above 100 are considered mission critical, while close to 70 is considered normal. Forest species established in 2005, have degree of disturbance and instability of the mass are; Vitex cymosa and Nectrandra membranaceae and species established in 2009 to further instability mass presented are: Pouteria capasifolia, Terminalia amazonia, Jacaranda copaia, Triplaris cumingiana and Aspidosperma laxiflorum. In relation to physical and chemical analysis of soil, in blocks where 29 forest species are established, show that the highest content of organic matter and nitrogen occurs in blocks species Platymiscium pinnatum, Persea sp., Albizia sp., Apeiba membranacea, Guarea kunthiana, Pouteria capasifolia, Heliocarpus americanus, Aspidosperma laxiflorum, Ochroma pyramidale, Pictocoma discolor and Remigia sp., this has allowed the species have good growth and development in relation to other species with low organic matter content and nitrogen. The result of the analysis is established as the baseline, it will allow future research to perform statistical analysis of correlation and regression, how involved in the growth of forest species.